DEVELOPMENT OF A DISCRIMINATORY METHOD FOR DETERMINATION OF IN VITRO DISSOLUTION OF CILNIDIPINE - Somasekhar, Vanita; H, Tejashwini; PV, Murali krishna (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study involves the development of a discriminatory method to differentiate the in vitro dissolution of cilnidipine’s mouth-dispersing film from that of a commercial tablet. Methods: The mouth-dispersing film was initially developed using a reported established method. A discriminatory dissolution method was developed to assess the in vitro dissolution of the mouth-dispersing film and compare the same with that of the commercial tablet. Results: The study findings indicated the method employed was able to differentiate the dissolution of the fast-dissolving film from the commercial tablet. About 98.52±0.60% of the drug was found to be released from the oral film in 40 min whereas the tablet took nearly 5 h for 92.06±0.49% of the drug to get released. Conclusion: These results demonstrate that the dissolution media identified was able to create the necessary sink condition that would be able to differentiate the dissolution profile of the mouth-dispersing film from the conventional tablet. The ultrasound spectrophotometric method employed was found to be simple rapid and sensitive enough to estimate the drug release from diverse pharmaceutical dosage forms.